PROSES KEPUTUSAN PEMBELIAN KONSUMEN DALAM MEMBELI PUPUK ORGANIK CAIR MEREK JIMMY HANTU DI TOKO BTA - Hapsari, Hepi; Alifia, Salma; Rasmikayati, Elly; Charina, Anne; Syamsiyah, Nur (Agros Journal of Agriculture Science, 2024)
The higher of human population encourages the fulfillment of food security. Food security globally and in Indonesia can be supported through green sustainable agricultural activities, either one is the use of liquid organic fertilizer. However, the use of liquid organic fertilizer is still not widely used in Indonesia (Serang City) and the sales are low. This study aims to analyze the decision process of purchasing Jimmy Hantu Liquid Organic Fertilizer (JH-LOF) at Bintang Tani Abadi (BTA) Agriiculture Store Serang City. This study used quantitative methods with explanatory survey that took data from 65 responndents. Data analysis uses descriptive statistical analysis to analyze the JH-LOF purchase decision process. The results showed that the JH-LOF purchase decision process carried out by consumers prioritized product quality and fertilizer use experience as a reference for purchasing.